2016
DOI: 10.3897/bdj.4.e7218
|View full text |Cite
|
Sign up to set email alerts
|

New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae)

Abstract: BackgroundThe genus Boletina is a species rich group of fungus gnats. Members of the genus are mainly known from temperate, boreal and arctic biomes. Phylogeny of the genus is still poorly resolved, dozens of species are insufficiently described and undescribed species are often discovered, especially from samples taken from the boreal zone.New informationFour new species are described. Boletina valteri Salmela sp.n. (Finland), Boletina kullervoi Salmela sp.n. (Finland), B. hyperborea Salmela sp.n. (Finland, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 968 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Gnoristinae is one of the most diverse and taxonomically difficult subfamilies of Mycetophilidae, with new species or genera being described almost every year (Niu et al ., ; Ševčík & Hippa, ; Kerr, , ; Ševčík et al ., ; Martinsson & Kjaerandsen, ; Kallweit, ; Salmela et al ., ). It is composed of over 440 species in approximately 29 extant genera.…”
Section: Introductionmentioning
confidence: 97%
“…Gnoristinae is one of the most diverse and taxonomically difficult subfamilies of Mycetophilidae, with new species or genera being described almost every year (Niu et al ., ; Ševčík & Hippa, ; Kerr, , ; Ševčík et al ., ; Martinsson & Kjaerandsen, ; Kallweit, ; Salmela et al ., ). It is composed of over 440 species in approximately 29 extant genera.…”
Section: Introductionmentioning
confidence: 97%
“…Borkent and Wheeler 2012, Kurina and Hippa 2015). In Europe fungus gnats probably display an anomalous gradient of species richness, that is, the number of species correlates positively with latitude (Salmela et al 2016). The northern boreal zone is probably the hot-spot of fungus gnat species richness (Kjærandsen et al 2007), and the Fennoscandian peninsula (Norway, Sweden, Finland, Kola peninsula and Russian Karelia) in total harbours about 1000 species, of which ca.…”
Section: Introductionmentioning
confidence: 99%
“…Sciophila larvae are mostly associated with fungal fruiting bodies, especially polypores, and most likely are spore-feeding (Jakovlev 2011) or may develop internally in fungus tissue (Zaitzev 1982). Three Boletina species are figured here and discussed; a review on the taxonomic status and ecology of the Holarctic species of the genus was recently provided (Salmela et al 2016). The genus Phronia is rich in species, having 112 and 97 named taxa in the Holarctic and Palaearctic regions, respectively (Gagné 1975, Jakovlev and Polevoi 2009, Ševčík 2009, Pape and Thompson 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogeny and natural classification of the genus are still unresolved (Martinsson et al 2011), and new species are regularly found, especially from the boreal zone (Salmela et al 2016). However, in a phylogenetic assessment based on molecular characters, the Boletina trivittata-group (consisting of B. trivittata and B. subtrivittata Zaitzev, 1994) formed a monophyletic clade (Martinsson et al 2011).…”
Section: Subfamily Gnoristinae Edwards 1925mentioning
confidence: 99%
“…obs.). Immature stages of B. joosti are unknown, but B. trivittata has been reared from rotting wood and soil litter; Boletina larvae are seldom found from fungal fruiting bodies (see Salmela et al 2016 for a review). Boletina joosti is probably a very rare species, perhaps having a restricted and fragmented Central European range in mountainous areas.…”
Section: Subfamily Gnoristinae Edwards 1925mentioning
confidence: 99%